English language policy in Thailand. Issue 1 (April 2017) - Baker, Will; Jarunthawatchai, Wisut
Abstract : The focus of this article is on English language policy in Thailand and education policy in particular as the most obvious manifestation of official overt language policy. As such English language education policy offers a lens through which to examine current language ideologies and the connections between language policy and practices. We place English within the wider linguistic landscape of Thailand in relation to Thai and other languages and explore the monolingual and monocultural ideologies that underpin much policy in this area. However, we also suggest that recent policy reflects an increasing awareness of multilingualism. Nonetheless, Thailand along with many other countries in ASEAN (Association of South East Asian Nations) has invested considerable resources and time in English, based on an underlying ideology that views English as the language of development and globalisation. At the same time, there has been persistent dissatisfaction with the perceived results of education practices as regards English proficiency levels. We argue that much of this supposedly low level of proficiency is due to inappropriate native speaker and Anglo-centric models of English which do not reflect the growing use of English as a lingua franca (ELF) globally and particularly as the official lingua franca of ASEAN. We also note the concerns that have been raised as regards the detrimental effects on other languages and areas of education resulting from an over-emphasis on English and the inequalities that this may reinforce.